Duvelisib: A 2018 Novel FDA-Approved Small Molecule Inhibiting Phosphoinositide 3-Kinases - Daniel A. Rodrigues; Fernanda S. Sagrillo; Carlos A. M. Fraga (MDPI AG, 2019)
Duvelisib (Copiktra®) is a dual inhibitor of phosphoinositide 3-kinases (PI3Kδ and PI3Kγ). In 2018, duvelisib was first approved by the Food and Drug Administration (FDA) for the treatment of adult patients with relapsed or refractory chronic lymphocytic leukaemia (CLL)/ small lymphocytic lymphoma (SLL) after at least two prior therapies. Duvelisib has also been approved under accelerated track for relapsed or refractory follicular lymphoma (FL) after at least two prior systemic therapies. In this review, we provide a series of information about duvelisib, such as the development of clinical trials for LLC/SLL and FL and the steps used for its synthesis.